High performance resorbable composites for load-bearing bone fixation devices. (May 2018) - Heimbach, Bryant; Tonyali, Beril; Zhang, Dianyun; Wei, Mei
Abstract: Bone fractures are some of the most common injuries annually, and many require a fixation device to help properly heal. The present study focuses on developing a bioresorbable composite that has high strength and stiffness for bone fixation applications. To achieve this, a design of experiments was performed, testing the effect of long fiber reinforcement type, matrix type, matrix amount, and particle reinforcement amount on the flexural properties of the composite. Based on these results, the ideal resorbable long fiber reinforcement, particle reinforcement, and matrix material are degummed silk fibroin, hydroxyapatite, and polylactic acid, respectively. Through further optimizations of the particle reinforcement phase a flexural modulus and strength of 13.7 GPa and 437 MPa, respectively, was achieved. Both values are among the highest found in literature, with the strength far exceeding the requirement for a fixation device and the highest for such a bioresorbable composite material, showing great promise for use as a bioresorbable fixation device. Graphical abstract: fx1